Обломов: роман в 4-х частях / И. А. Гончаров - Гончаров Иван Александрович (Удмуртия, 1988)
Экземпляры: ф. 4 (20210111) / Инвентарный номер: 95890 / Цена: 10.00 / Авт.знак: Г 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1